A Study on the Key Skilled Labour Shortage for the Sustainability of the Construction Industry in Sri Lanka - Ratyanake, Clement Lal Ashley (2024)
The construction industry, through effective management processors and sustainable development principles, can produce benefits across all economic, social, and environmental elements. Skilled workers, particularly for the construction industry, are considered a primary resource that can have a direct bearing on the success of construction projects. The intriguing, complex and schedule driven nature of the industry is often subject to varying levels of complications mostly emanating from labour related issues, invariably causing implications for performance, viability, and sustainability. Construction globally is considered as a vibrant manufacturing industry considerably contributing to national economies in addition to providing employment to vast numbers of people. From a Sri Lankan perspective the industry is considered a key segment contributing well over 7% to the nations GDP. After the end of three decades of hostility and limitations to economic growth and development, the last two decades has recorded significant progress particularly in the construction sector with vast numbers of foreign investors also showing a keen interest and providing ample competition to the local real estate developers. With the surge of the industry, the shortfalls of the “Labour force” has emerged as a serious detriment with simultaneous effects also highlighting limitation of “Skilled Labour” as a serious drawback to the local construction sector. This has resulted in the identification of a substantial array of contributory reasons and the importance of finding solutions to the problems to ensure the continuation and momentum of the construction industry. Therefore, the purpose of this review considering all factors, is objectively focused in studying from a broader aspect the shortage of skilled workers and underlines the seriousness of the problem of not being able to attract the youth, unemployed and career seekers to train, retain and importantly set in place proper secondary and formal education systems in line with Sri Lankan construction industry wants. Findings will make it possible for policy makers, industry professionals, practitioners, and future researchers to use this as a reliable foundation for further analysis and studies.